2016
DOI: 10.2113/econgeo.111.5.1241
|View full text |Cite
|
Sign up to set email alerts
|

Lithogeochemical Vectors for Hydrothermal Processes in the Strange Lake Peralkaline Granitic REE-Zr-Nb Deposit

Abstract: 21Extreme enrichment and post-magmatic hydrothermal mobilization of the rare earth 22 elements (REE), Zr and Nb have been reported for a number of anorogenic peralkaline 23 intrusions, including the world-class REE-Zr-Nb deposit at Strange Lake, Quebec, 24Canada. Establishing lithogeochemical vectors for these types of deposits is a challenging 25 task because the effects of hydrothermal processes on element distribution are poorly 26 known and the relationships of alteration types to mineralization stages hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 34 publications
2
61
0
2
Order By: Relevance
“…It would also 577 indicate that ƒO 2 was no longer buffered by Reaction 3 and that alteration of arfvedsonite to 578 aegirine had ceased before entrapment of Group 3 inclusions. Gysi et al (2016) showed that 579 arfvedsonite in the Strange Lake granites and pegmatites underwent three types of alteration, 580 namely pervasive replacement by aegirine, core-replacement by hematite and rim replacement by 581 aegirine ± hematite. We propose that these different types of alteration reflect different physico-582 29 chemical conditions, and that at relatively high temperature arfvedsonite was replaced by 583 aegirine, whereas at lower temperature it was replaced by aegirine and/or hematite.…”
Section: (Reaction 3) 572mentioning
confidence: 99%
“…It would also 577 indicate that ƒO 2 was no longer buffered by Reaction 3 and that alteration of arfvedsonite to 578 aegirine had ceased before entrapment of Group 3 inclusions. Gysi et al (2016) showed that 579 arfvedsonite in the Strange Lake granites and pegmatites underwent three types of alteration, 580 namely pervasive replacement by aegirine, core-replacement by hematite and rim replacement by 581 aegirine ± hematite. We propose that these different types of alteration reflect different physico-582 29 chemical conditions, and that at relatively high temperature arfvedsonite was replaced by 583 aegirine, whereas at lower temperature it was replaced by aegirine and/or hematite.…”
Section: (Reaction 3) 572mentioning
confidence: 99%
“…The REE commonly occur in trace concentrations in the earth's crust [3], while economic REE deposits typically are associated with carbonatite and alkaline/peralkaline igneous systems at intraplate tectonic settings. Prominent examples include Bayan Obo in China [2], Strange Lake and Nechalacho in Canada [4][5][6][7], Mountain Pass, CA [8], and Bear Lodge, WY, in the USA [9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also indicated the importance of hydrothermal processes for the mobilization and concentration of the REE in the late magmatic evolution stages of carbonatite and alkaline/peralkaline systems [4,5,[16][17][18][19]. Secondary REE enrichment can be significant in the late stages of pluton emplacement, as evidenced by the Strange Lake REE-Zr-Nb deposit in Canada, where metasomatic processes led to hydrothermal mobilization and mineralization of the REE at the periphery of the pluton [4,5,16,17]. Similar metasomatic processes were observed in the Tamazeght alkaline HFSE/REE-enriched pluton in Morocco [20] and other deposits [2,4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of HFSE to enhanced grades in alkaline intrusions is generally thought to be caused by magmatic fractionation, but mineralogical and petrologic evidence often points to post-magmatic pneumatolytic or hydrothermal processes. Post-magmatic mineralization events are commonly associated with intensive and highly variable alteration types of both intrusive and wall rocks, thereby superimposing primary petrographic features [1,2,6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%